Development (Paradigm) Failures - Roland Hodler (Swiss National Bank, Study Center Gerzensee, 2011)
Over time the international development community has advocated various development paradigms, but countries following these paradigms have often performed poorly. I provide an explanation for this poor performance. In my model the political leader of a developing country chooses a policy and whether to implement it in an honest or corrupt manner. These choices affect domestic production and aid inflows. Production is high when productive capacity is high, and when the policy is appropriate in the country-specific circumstances and implemented honestly. Aid inflows are high when the policy is close to the paradigm. In equilibrium countries with low productive capacity and high corruption resulting from weak political institutions follow the paradigm more closely. Hence my model suggests that development paradigms have a tendency to fail because they are primarily followed by countries that would fail anyway.
Keywords: D70; O10; O40; 330; Economic development; Development paradigms; Foreign aid; Entwicklungshilfe; Wirkungsanalyse; Neue politische Ökonomie